2023
DOI: 10.3390/nano13040753
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for the Synthesis of a Coral-like Boron Nitride Micro-/Nanostructure Catalyzed by Fe

Abstract: Catalyzed by Fe, novel a coral-like boron nitride (BN) micro-/nanostructure was synthesized from B2O3 by a ball milling and annealing process. Observations of the morphology of the product indicated that the coral-like BN micro-/nanostructure consists of a bamboo-shaped nanotube stem and dense h-BN nanoflakes growing outward on the surface of the nanotube. Experimental results showed that the morphology of the BN nanotube was greatly dependent on the anneal process parameters. With the annealing time increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Similar structures also bring similar physical and chemical properties, such as excellent thermal conductivity and mechanical properties. At the same time, BN also has many properties that carbon materials do not have, including good thermal stability, chemical stability and macroscopic transmittance to visible light [ 9 , 10 , 11 ]. Taken together, it can be found that boron nitride is very suitable as the internal heat transfer material of PiG and can also play a certain role in enhancing the mechanical properties of PiG [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar structures also bring similar physical and chemical properties, such as excellent thermal conductivity and mechanical properties. At the same time, BN also has many properties that carbon materials do not have, including good thermal stability, chemical stability and macroscopic transmittance to visible light [ 9 , 10 , 11 ]. Taken together, it can be found that boron nitride is very suitable as the internal heat transfer material of PiG and can also play a certain role in enhancing the mechanical properties of PiG [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%